Consistent global dataset on biodiversity intactness footprint of agricultural production from 2000 to 2020 - Nguyen, Can Trong; Vačkářová, Davina; Weinzettel, Jan (Scientific data, 2025)
Global biodiversity is rapidly declining, primarily due to agricultural production driven by both domestic and transboundary consumption. This study addresses the challenges posed by inconsistent spatiotemporal biodiversity data by developing a time series of biodiversity loss footprints based on Biodiversity Intactness Index (BII). Numerous land use, land cover, and auxiliary datasets were integrated to produce a consistent time series of high-resolution harmonized land use (HHLU) maps. These maps were utilized to quantify spatial BII using linear-mixed effect models. Biodiversity intactness loss (BII footprint) was subsequently attributed to specific crops and livestock commodities. This study provides comprehensive global datasets, including HHLU and BII maps, and synthesized BII footprints across 14 biomes, 193 countries and territories, 154 crop items, and 9 livestock categories from 2000 to 2020. These datasets facilitate spatiotemporal analyses to identify trends and patterns in global biodiversity integrity and biodiversity footprints, thereby elucidating the ecological trade-offs embedded in international trade. These insights can encourage appropriate interventions to transform consumption patterns and supply chains toward the effective conservation of global biodiversity.
Keywords: zemědělské plodiny; Animals; Biodiversity; Crops, Agricultural; Livestock; Agriculture; dobytek; Conservation of Natural Resources; biodiverzita; zachování přírodních zdrojů; zvířata; zemědělství